Better Lives for Dogs: Incorporating Human Behaviour Change Into a Theory of Change to Improve Canine Welfare Worldwide - Reed, Karen; Upjohn, Melissa M. (Frontiers in Veterinary Science, 2018)
The world’s estimated 600million dogs face a range of welfare issues which vary according to local context and locally accepted norms regarding attitudes towards dogs. Dogs Trust Worldwide, an international Non-Governmental Organisation which works to improve canine welfare, is applying a Theory of Change framework to define and unpick key challenges faced when collaborating with local partners to achieve its mission. We describe the Theory of Change approach and the importance of Human Behaviour Change within this. We identify questions which need to be addressed as part of articulating our ways of working with partner organisations and acknowledge issues around generating evidence to measure the impact our work has on the ultimate beneficiaries.